This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Loved this solution.
Nice solution :)
How was the root in the denominator divided by u? This is probably simple, but I don't get it.
Log in to reply
∣ u ∣ = u 2 being u a real number
Log in to reply
And the -2u?
Log in to reply
@Yihan Xia – you have to divide numerator and denomiator by u for that it is good. In this case, as u → ∞ you can consider u positive and u 2 − 2 u positive and therefore , here being a and b real positive numbers b a = b a
The sq rt of 1+(2*-1) is an imaginary number so that is the CLOSEST to the origin that the equation can be solved and is the limit. Is that correct? In other words as long as the integer is -2 or smaller, the equation works and -1 or 0 it fails?
Log in to reply
I don't understand you, sorry... I'm trying it but I don't get it, sorry.
One way to solve the problem: make the substitution, u = − x . Then the problem becomes u → + ∞ lim u 2 − 2 u − u
= lim u → ∞ u ( 1 − u 2 − 1 )
= u → ∞ lim u 1 1 − u 2 − 1
= lim t → 0 t 1 − 2 t − 1 ( t = 1 / u )
= lim t → 0 2 1 − 2 t − 2 ( L’Hopital’s Rule )
= − 1
Note: it is much easier to solve the problem if we notice at step 1 that lim u → + ∞ u 2 − 2 u − u = lim u → + ∞ u 2 − 2 u + 1 − u since u goes to infinity. But this intuitively clear step requires some justification.
L'Hopital's rule is efficient and can solve some limit problems not readily treated otherwise, but it seldom gives any insight.
I use this often as u → ∞ lim u 2 − 2 u = u → ∞ lim u 2 − 2 u + 1
I cheat on these. Simply substitute a fairly large -x. Here -10 is big enough, yielding (80)^1/2-10~9-10=-1.
When x is negative then x = − x 2 . Rationalizing the numerator, one gets x 2 + 2 x − x 2 x . Dividing the top and bottom both by x means dividing the bottom by − x 2 . One gets − 1 + x 2 − 1 2 , so the limit is − 1 .
Won't a much simpler solution be to rewrite the body of the limit as ( x + 1 ) 2 − 1 + x ∼ ∣ x + 1 ∣ + x as ∣ x ∣ → ∞ ? As x → − ∞ , we have ∣ x + 1 ∣ + x ∼ − x − 1 + x = − 1 .
you could go the long way and go lim x → − ∞ ( f ( x + δ x ) − f ( x ) ) / δ x and work your way through it, perhaps do a Taylor expansion, but you'll find that a couple of substitutions, say x=-10 and x=-100 shows this sequences quickly converges to − 1 a s x → − ∞
mana yang dari Indonesia....
Problem Loading...
Note Loading...
Set Loading...
Make the substitution u = - x, then x → − ∞ lim x 2 + 2 x + x = u → ∞ lim u 2 − 2 u − u = u → ∞ lim u 2 − 2 u + u ( u 2 − 2 u − u ) ⋅ ( u 2 − 2 u + u ) = u → ∞ lim u 2 − 2 u + u − 2 u = Now, let's divide numerator and denominator by u = u → ∞ lim 1 − u 2 + 1 − 2 = − 1